2022
DOI: 10.1093/ajcn/nqac008
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition-related claims lead parents to choose less healthy drinks for young children: a randomized trial in a virtual convenience store

Abstract: Background Consumption of sugar-sweetened beverages, including fruit drinks (i.e., fruit-flavored drinks containing added sugar), contributes to childhood obesity. Objectives We aimed to examine whether nutrition-related claims on fruit drinks influence purchasing among parents and lead to misperceptions of healthfulness. Methods We conducted an experiment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 50 publications
0
25
1
Order By: Relevance
“…Claim and imagery removal had no knowledge or health perception effects combined or independently. While previous findings on whether fruit imagery impacts health perceptions are mixed, 13,44 our findings differ from previous studies that found that nutrient content claims, 15 100% vitamin C claims in particular, 18,44 increased perceptions that drinks were healthy and selection of high-added sugar beverages. These differences are likely due to product type (branded vs mock or unbranded products) and choices offered (many different beverages vs 1 other beverage).…”
Section: Jama Network Open | Pediatricscontrasting
confidence: 99%
See 1 more Smart Citation
“…Claim and imagery removal had no knowledge or health perception effects combined or independently. While previous findings on whether fruit imagery impacts health perceptions are mixed, 13,44 our findings differ from previous studies that found that nutrient content claims, 15 100% vitamin C claims in particular, 18,44 increased perceptions that drinks were healthy and selection of high-added sugar beverages. These differences are likely due to product type (branded vs mock or unbranded products) and choices offered (many different beverages vs 1 other beverage).…”
Section: Jama Network Open | Pediatricscontrasting
confidence: 99%
“…9,11,12 Research has shown that this marketing misleads consumers. [13][14][15][16][17][18] In a 2022 study, 18 parents who viewed fruit drinks with claims were more likely to incorrectly believe that these products did not contain added sugar or were 100% juice. Correcting these misperceptions could enhance parents' knowledge and encourage healthier beverage purchases.…”
Section: Introductionmentioning
confidence: 99%
“…However, while a nutrient claim might be truthful in terms of a specific nutrient (“0% trans-fat”), this study suggests that the presence of the claim boosts purchase intention and perceived healthfulness, for products that may have excess content of other critical nutrients such as sugars, saturated fats or sodium. This “halo effect” of nutrient claims has been demonstrated to lead consumers to overestimate the nutritional quality of food products ( 9 , 10 , 31 ), reduce the efficacy of FOP labels when claims refer to the same nutrient that is warned on the FOP label ( 32 ), ultimately inducing consumers to purchase products that are excessive in critical nutrients. This result underscores the importance of promoting strict regulations that prohibit the use of health or nutrition claims on products with excessive content of one or more critical nutrients, as has been regulated recently in Argentina ( 15 ) and implemented in other countries such as Australia, New Zealand ( 33 ) and Mexico ( 13 ), as well as the need for labeling policies and regulations to be more coherent with other policies aimed at promoting healthy diets.…”
Section: Discussionmentioning
confidence: 99%
“…Here is an example of our current situation: "Nutrition-related claims led parents to choose less healthy beverages for their children and misled them about the healthfulness of fruit drinks. Labeling regulations could mitigate misleading marketing of fruit drinks" (Hall et al 2022).…”
Section: Public Health Advertisingmentioning
confidence: 99%